2018
DOI: 10.1007/s00429-018-1700-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual brain plasticity induced by central and peripheral visual field loss

Abstract: Disorders that specifically affect central and peripheral vision constitute invaluable models to study how the human brain adapts to visual deafferentation. We explored cortical changes after the loss of central or peripheral vision. Cortical thickness (CoTks) and resting-state cortical entropy (rs-CoEn), as a surrogate for neural and synaptic complexity, were extracted in 12 Stargardt macular dystrophy, 12 retinitis pigmentosa (tunnel vision stage), and 14 normally sighted subjects. When compared to controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 101 publications
1
13
0
Order By: Relevance
“…One possible explanation for the difference in findings is that we did not assess the onset, duration, severity and treatment of these ophthalmic conditions in this study. Previous studies show that correcting cataract with surgery is associated with better cognitive performance and increased grey matter volume in the visual cortex ( 36–40 ). With our data also showing that moderate-to-severe, but not mild, visual impairment is associated with higher risk of dementia, it would be of interest to further examine whether early treatment of poor vision might help delay or prevent clinical manifestation of dementia in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the difference in findings is that we did not assess the onset, duration, severity and treatment of these ophthalmic conditions in this study. Previous studies show that correcting cataract with surgery is associated with better cognitive performance and increased grey matter volume in the visual cortex ( 36–40 ). With our data also showing that moderate-to-severe, but not mild, visual impairment is associated with higher risk of dementia, it would be of interest to further examine whether early treatment of poor vision might help delay or prevent clinical manifestation of dementia in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…122 Importantly, several MRI studies have described a degree of plasticity/remodelling following visual field defects in RCD or MD, and also with congenital visual impairment, including in ACHM. [123][124][125] The remapping of the primary visual cortex (V1) consists of a shift of central retinal inputs to more peripheral locations in V1, and this phenomenon was found to be larger in patients with more constricted visual fields. 125 However, it was noted that individuals with RCD did not have marked structural differences compared with controls (changes in white matter were mild); but in contrast, individuals with early-onset visual loss had thickened striate cortical and grey matter.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Two studies 28,29 have compared BOLD responses in the visual cortex before and after retinal prosthetic implants and demonstrated that a degree of visual cortical plasticity is indeed possible in adults who have experienced complete blindness for several years. Evidence for plasticity is also available for adult patients with residual central vision, whose occipital cortex undergoes an apparent reorganization of retinotopic maps; in these patients, the representation of the central visual field spreads over the peripheral region, which is deprived of its normal visual input 30,31 ; there are also structural changes, affecting cortical thickness 32 ; however, the mechanisms underlying this reorganization are debated. 33 In addition, these patients show evidence for cross-modal plasticity, 28 whereby the deafferented peripheral representation may become responsive to nonvisual signals, and these signals may interact competitively with visual signals from the spared visual field.…”
mentioning
confidence: 99%